2000
DOI: 10.2170/jjphysiol.50.215
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transepithelial lon Transport by Secretin in Human Intestinal Caco-2 Cells.

Abstract: Secretin is a peptide hormone which is secreted from duodenal endocrine-type cells (S cells) and stimulates the secretion of bicarbonate-rich pancreatic juice [1]. Secretin is composed of 27 amino-acid residues [2], exhibiting structural and functional similarities to vasoactive intestinal polypeptide (VIP) [3,4]. The secretin receptor has been shown to be coupled to a Gprotein which activates adenylate cyclase to increase cytosolic cyclic AMP (cAMP) concentration [5][6][7]. In pancreatic duct cells, secretin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The observed predominant Cl -secretion elicited by TMP in T84 cells was consistent with the Cl --secreting characteristics of this colonic crypt-like cell model. Although secretory properties were less well characterized in Caco-2 cells, a previous study [26] has demonstrated I SC increases in response to cAMP-evoking agents including PDE inhibitor, 3-isobutyl-1-methylxanthine (IBMX), in Caco-2 cells with biphasic current kinetics and DIDS sensitivity similar to that of the TMP-induced I SC response observed in the present study. Interestingly, in the same study alkalization of the apical solution could be induced which was also inhibited by basolateral addition of DIDS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The observed predominant Cl -secretion elicited by TMP in T84 cells was consistent with the Cl --secreting characteristics of this colonic crypt-like cell model. Although secretory properties were less well characterized in Caco-2 cells, a previous study [26] has demonstrated I SC increases in response to cAMP-evoking agents including PDE inhibitor, 3-isobutyl-1-methylxanthine (IBMX), in Caco-2 cells with biphasic current kinetics and DIDS sensitivity similar to that of the TMP-induced I SC response observed in the present study. Interestingly, in the same study alkalization of the apical solution could be induced which was also inhibited by basolateral addition of DIDS.…”
Section: Discussionsupporting
confidence: 64%
“…Possible candidates of physiological regulators may include prostaglandins, VIP and secretin, all of which are known to be present in the colon and able to increase intracellular cAMP [30][31][32] . In fact, secretin has been shown to stimulate Cl -secretion in the colon [33] and HCO 3 -secretion in Caco-2 cells [26] . It should be noted that TMP has been shown to be a cAMP-evoking agent having an action similar to PDE inhibitor in antiplatelet activity [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an amiloride-sensitive channel has been identified in H441 and A549 cells using patch clamp and Ussing chamber techniques by several groups (2,3,6,28,(31)(32)(33). This is the first report of ENaC mRNA expression in Caco-2 cells, although a benzamil-sensitive short circuit current has been reported (34,35). A novel finding of this study was that the ␦-subunit is co-expressed with ␣-, ␤-, and ␥-ENaC in the native human epithelial cells we examined.…”
Section: Discussionmentioning
confidence: 88%
“…Since many GPCRs, including the the VIP receptor [38], secretin receptor [59], β adrenergic receptor [60], muscarinic acetylcholine receptor [61], protease-activated receptors [35], and purinergic receptors [37] regulate ion transport in enterocytes it is very feasible that PAF does the same. In order to verify this expectation we investigated PAF-induced transepithelial ion transport and have found that indeed PAF activates a transepithelial ion flux in HT29-Cl19A polarized colonic epithelial monolayers [25].…”
Section: Regulation Of Epithelial Ion Transport By Pafmentioning
confidence: 99%
“…More importantly from the point of view of enteral health, PAFR activation leads to intestinal TNFα, PLA2-II, PAFR gene expression in an in vivo, PAF-perfusioninduced bowel necrosis model [66][67][68]. As discussed above, signaling via the PAFR results in the activation of transcription factors such as STAT [55] and NFĸB [58,59]. These transcription factors are likely to play major roles in PAF-induced gene expression regulation.…”
Section: Regulation Of Epithelial Gene Expression By Pafmentioning
confidence: 99%